Measurements of Tendon Movement Within the Bicipital Groove After Suprapectoral Intra-articular Biceps Tenodesis in a Cadaveric Model. Issue 1 (21st January 2021) - Kelly, Brian J.; Reynolds, Alan W.; Schimoler, Patrick J.; Kharlamov, Alexander; Miller, Mark Carl; Akhavan, Sam
Background: Lesions of the long head of the biceps can be successfully treated with biceps tenotomy or tenodesis when surgical management is elected. The advantage of a tenodesis is that it prevents the potential development of a cosmetic deformity or cramping muscle pain. Proponents of a subpectoral tenodesis believe that "groove pain" may remain a problem after suprapectoral tenodesis as a result of persistent motion of the tendon within the bicipital groove. Purpose/Hypothesis: To evaluate the motion of the biceps tendon within the bicipital groove before and after a suprapectoral intra-articular tenodesis. The hypothesis was that there would be minimal to no motion of the biceps tendon within the bicipital groove after tenodesis. Study Design: Controlled laboratory study. Methods: Six fresh-frozen cadaveric arms were dissected to expose the long head of the biceps tendon as well as the bicipital groove. Inclinometers and fiducials (optical markers) were used to measure the motions of the scapula, forearm, and biceps tendon through a full range of shoulder and elbow motions. A suprapectoral biceps tenodesis was then performed, and the motions were repeated. The motion of the biceps tendon was quantified as a function of scapular or forearm motion in each plane, both before and after the tenodesis. Results: There was minimal motion of the native biceps tendon during elbow flexion and extension but significant motion during all planes of scapular motion before tenodesis, with the most motion occurring during shoulder flexion-extension (20.73 ± 8.21 mm). The motion of the biceps tendon after tenodesis was significantly reduced during every plane of scapular motion compared with the native state ( P < .01 in all planes of motion), with a maximum motion of only 1.57 mm. Conclusion: There was a statistically significant reduction in motion of the biceps tendon in all planes of scapular motion after the intra-articular biceps tenodesis. The motion of the biceps tendon within the bicipital groove was essentially eliminated after the suprapectoral biceps tenodesis. Clinical Relevance: This arthroscopic suprapectoral tenodesis technique can significantly reduce motion of the biceps tendon within the groove in this cadaveric study, possibly reducing the likelihood of groove pain in the clinical setting.